What is the Marketing Strategy for Red Corner Café - Kune, Debiyanti; Dg. Maserre, Hasnawati A.; Saliani, Widia Adisti; Aulia Putri, Jesica Rvani (Journal of Management, 2024)
Red Corner, a restaurant in Makassar City, has drawn foodies with its distinctive Molecular Gastronomy-based cuisine and exclusive culinary concept. Even though they are successful in drawing patrons, restaurants nevertheless have a difficult time keeping up with demand because of space constraints and lengthy lines, which can negatively affect the dining experience. The purpose of this study is to analyze Red Corner's marketing strategy utilizing the SWOT method. This study investigates strategic prospects for optimization and determines the elements influencing consumer interest in Red Corner through observations based on customer evaluations and comments on the Beautiful Indonesia platform. Red Corner hopes to use the research findings to improve its marketing tactics, put more of an emphasis on client satisfaction, and reach a wider audience. In addition to helping Red Corner, this study project aims to shed light on restaurant marketing tactics and customer service from both a theoretical and practical standpoint